Responsive materials and methods : state-of-the-art stimuli-responsive materials and their applications - Tiwari, Ashutosh; Kobayashi, Hisayoshi (Hoboken, New Jersey : Scrivener Publishing : John Wiley & Sons, Inc, 2014)
"The development of finely-tuned materials that adjust in a predictable manner by specific environment change is the recent arena of materials research. It is a newly emerging supra-disciplinary field with huge commercial potential. Stimuli-responsive materials answer by a considerable change in their properties to small changes in their environment. Responsive materials are becoming increasingly more prevalent as scientists learn about the chemistry and triggers that induce conformational changes in materials structures and devise ways to take advantage of and control them. Responsive Materials and Method offers state-of-the-art of the stimuli-responsive materials and their potential applications. This collection brings together novel methodologies and strategies adopted in the research and development of responsive materials and technology"--
Part 1. Stimuli-responsive polymeric materials -- part 2. Smart nano-engineered materials -- part 3. Smart biosystems engineering -- part 4. Theory and modeling.
Includes bibliographical references and index.
Online resources; title from PDF title page (Wiley, viewed November 8, 2013).
Keywords: Smart materials; Polymers; Nanostructured materials; TECHNOLOGY & ENGINEERING -- Material Science; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Nanostructured materials; Polymers; Smart materials; Polymerer; Electronic books; Electronic books